The strange case of Origami Yoda - Angleberger, Tom (New York : Amulet Books, 2010)
Sixth-grader Tommy and his friends describe their interactions with a paper finger puppet of Yoda, worn by their weird classmate Dwight, as they try to figure out whether or not the puppet can really predict the future. Includes instructions for making Origami Yoda.
Texas Bluebonnet Award nominee, 2011-2012.
Lexile
Accelerated Reader
Accelerated Reader AR
Texas Bluebonnet Award winner, 2012.
Keywords: Yoda -- (Fictitious character from Lucas) -- Juvenile fiction; Finger puppets -- Juvenile fiction; Origami -- Juvenile fiction; Eccentrics and eccentricities -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Texas Bluebonnet Award nominee, 2011-2012.; Texas Bluebonnet Award winners